Pelatihan dan Pendampingan Pembukuan Keuangan Digital Menggunakan Aplikasi YouTap POS pada the Pituin Coffee House - Irsan Herlandi Putra; Hamidah Hamidah; Junaedi Abdillah; Muhtarudin Muhtarudin (FKIP, Universitas Palangka Raya, 2025)
Micro, small, and medium enterprises (MSMEs) have an important role in the Indonesian economy, but many business actors still face challenges in systematic and transparent financial records. The Pituin Coffee House, as one of the MSMEs in the culinary sector, faces obstacles in managing bookkeeping effectively. Therefore, digital financial bookkeeping training and assistance are carried out using the YouTap POS application to improve the efficiency and accuracy of financial records. The methods used in this activity include training sessions, hands-on practice, and intensive mentoring to ensure optimal understanding and implementation. The results of this program show that the use of the YouTap POS application is able to improve financial management skills, make it easier to monitor transactions, and support better business decision-making. With the digitization of bookkeeping, it is hoped that MSMEs such as The Pituin Coffee House can be more developed and competitive in the digital era.